Postblink Changes in the Ocular Modulation Transfer Function Measured by a Double-Pass Method - Montes-Mico, Robert; Alio, Jorge L; Charman, W. Neil (Investigative ophthalmology & visual science, 2005)
To examine the temporal changes in the modulation transfer function (MTF) of the eye after a blink. The distance MTF of a 5-mm pupil was derived from double-pass retinal images in 20 healthy young subjects at various intervals after a blink (1 second up to 15 seconds). Such measurements include the effects of wavefront aberration, scattered light, and errors in focus and are thus more relevant to real life than are estimates of MTF based on wavefront errors alone. Optimal MTF by a variety of criteria was found some 6 seconds after a blink. Inclusion of the effects of stray light and errors of focus does not affect the finding that optimal retinal image quality occurs some time after a blink. It does not appear that a loss in optical quality is the trigger of normal blinking.